The Impact of FinTech on Financial Sustainability and Digital Transformation in Emerging Economies: A Comparative Analysis Across Regions - Hassouna, Mohamed; Mohammed, Sara (PT. Teknologi Futuristik Indonesia, 2025)
Financial Technology (FinTech) has been a revolutionary force in the last ten years, especially in emerging economies that are working to expedite digital transformation and attain financial sustainability. This study examines how FinTech development affects financial sustainability, using institutional preparedness as a moderating variable and digital transformation as a mediating factor. The study uses fixed-effects panel regression analysis to investigate cross-regional dynamics using a panel dataset of 18 rising economies in Africa, the Middle East, and Southeast Asia from 2015 to 2025. FinTech development considerably improves financial sustainability, according to empirical studies (β = 0.42, p < 0.001), with digital transformation processes mediating about 38% of this benefit. This association is further strengthened by institutional preparedness, suggesting that regulatory frameworks and governance quality are crucial for maintaining FinTech-driven growth. Southeast Asia has the strongest correlation between FinTech adoption and sustainability, according to regional studies, whereas Sub-Saharan Africa's influence is still limited by policy and infrastructure constraints. The results highlight how FinTech may promote equitable and sustainable financial systems when it is backed by strong digital governance. It is recommended that policymakers advance financial literacy, improve digital infrastructure, and include ESG principles into FinTech regulations. This study advances our theoretical and practical knowledge of how FinTech may promote digital inclusion, economic resilience, and sustainable financial growth in developing nations.